Preliminary assessment of the solar resource in the United Kingdom. Issue 2 (7th September 2018) - Dhimish, Mahmoud; Holmes, Violeta; Mather, Peter; Sibley, Martin
Abstract: Solar radiation resources data are the foundation of knowledge for programs of large-scale deployment of solar energy technologies. This article summarizes the analysis of a new weather stations network in the United Kingdom. The analysis used three years (January 2015–December 2017) of data from 27 weather stations distributed across the country. The data comprises global horizontal irradiance (GHI), diffuse horizontal irradiance, direct normal irradiance and the ambient temperature. Network design, implementation and data quality assurance are described to document the network extent and quality. From all observed datasets, we found that Plymouth (located in southwest England) has the dominant GHI and ambient temperature among all other 26 locations. The least GHI is observed for Aberdeen (located in northeast Scotland) estimated at 77.3 kWh/m 2 . The least average ambient temperature is equal to 9.1°C; the data were detected by the weather station located in the capital of Scotland (Edinburgh). Although continued measurements are needed to understand the interannual resource variability, the current study should have significant applications for preliminary technology selection, power plant modeling and resource forecasting.